Quality in university higher education in times of pandemic: A student perspective - Moscoso-Paucarchuco , Ketty Marilú (2021)
Objective:  to measure the quality of university higher education in times of pandemic, in four universities in the Junín region, during the 2021 period, from a student position.  Material and methods: The scientific research method of applied type, descriptive level, quantitative design, of a single variable was used; in a mixed sample of non-inferential students. Results: the university student knows the academic objectives of his university and that these should be oriented to quality management; regarding the educational offer, many ignore its content; infrastructure and maintenance services have been stopped due to the pandemic; teachers carry out and execute scientific research, which is published in the repositories of each institution; Most of them comply with the profile detailed in University Law 30220; ancillary services must be translated into virtual form; Under these circumstances, the job market is one of the main interests of the student body: transparency shows a certain weakness, due to lack of communication and socialization of decisions made by university authorities. Conclusions: The majority of students are satisfied with the efforts made to fulfill academic activities in times of pandemic.